Brillouin cavity optomechanics with whispering-gallery microresonators - Enzian, GPA (2020)
Cavity quantum optomechanics is a field of investigation which studies the interaction between optical and mechanical degrees of freedom applying the powerful methods of quantum optics. These theoretical methods and experimental techniques have been developed through the second half of the 20th century and gained significant momentum following the invention of the laser. Upon the realisation that coherent manipulation of the motion of mesoscopic, or even macroscopic, mechanical systems was feasible using laser light, interest in cavity quantum optomechanics grew and groups across the globe began working towards the preparation of non-classical mechanical states. The field is now well established, but the preparation of non-classical states of the motion via interaction with optical fields remains challenging to explore, which is believed will open the door to studies of fundamental physics regarding decoherence, the quantum-to-classical transition or may even shed light on the interface between quantum mechanics and gravity.